Norms, gender, and payment method affect extraction behavior in a framed field experiment on community forestry in India - Zhang, Wei; Meinzen-Dick, Ruth S.; Valappanandi, Sanoop; Balakrishna, Raksha; Reddy, Hemalatha; Janssen, Marco A.; Thomas, Liya; Priyadarshini, Pratiti; Kandikuppa, Sandeep; Chaturvedi, Rahul; Ghate, Rucha (International Food Policy Research Institute, 2021)
This paper presents results from a framed field experiment in which participants make decisions about extraction of a common-pool resource, a community forest. The experiment was designed and piloted as both a research activity and an experiential learning intervention during 2017-2018 with 120 groups of resource users (split by gender) from 60 habitations in two Indian states, Andhra Pradesh and Rajasthan. We examine whether local beliefs and norms about community forest, gender of participants, within-experiment treatments (non-communication, communication, and optional election of institutional arrangements (rules)) and remuneration methods affect harvest behaviour and groups’ tendency to cooperate. Furthermore, we explore whether the experiment and subsequent community debriefing had learning effects. Results reveal a “weak” Nash Equilibrium in which participants harvested substantially less than the Nash prediction even in the absence of communication, a phenomenon stronger for male than female participants in both states. For male groups in both states, both communication and optional rule election are associated with lower group harvest per round, as compared to the reference non-communication game. For female groups in both states, however, communication itself did not significantly slow down resource depletion; but the introduction of optional rule election did reduce harvest amounts. For both men and women in Andhra Pradesh and men in Rajasthan, incentivized payments to individual participants significantly lowered group harvest, relative to community flat payment, suggesting a possible “crowding-in” effect on pro-social norms. Despite the generally positive memory of the activity, reported actual changes are limited. This may be due to the lack of follow-up with the communities between the experiment and the revisit. The fact that many of the communities already have a good understanding of the importance of the relationships between (not) cutting trees and the ecosystem services from forests, with rules and strong internal norms against cutting that go beyond the felling of trees in the game, may have also meant that the game did not have as much to add. Findings have methodological and practical implications for designing behavioral intervention programs to improve common-pool resource governance.